[LB.03.02] CHRONIC HYPERTENSION IN PREGNANCY: A TEN YEARS EXPERIENCE. (September 2017) - Agostinis, M.; Moretti, S.; Tandurella, N.; Grossi, A.; Cavallaro, G.; Pierobon, V.; Tavecchia, L.; Mancuso, V.; Mongiardi, C.; Montalbetti, L.; Lippi, A.; Grandi, A.M.; et al.
Abstract : Objective: Hypertension affects 10% of pregnancies with rising incidence in recent years; it represents a major cause both of maternal and fetal morbidity and mortality. Aim of our study was to evaluate, retrospectively, the incidence of gestational hypertension (GH) and preeclampsia (PE) in a sample of patients with chronic hypertension (CH). We also evaluated the relationship between antihypertensive therapy and development of complications during pregnancy. Design and method: We retrospectively enrolled 77 pregnant patients with CH (82 pregnancies). Patients were re-classified at the end of pregnancy in three groups: CH, GH, PE. For each patient, we evaluated office blood pressure (OBP) every 4 weeks until the 20th week, every two weeks until the end of pregnancy and 24 hours ambulatory blood pressure monitoring (24h-ABPM). We also assessed proteinuria in the same periods. Results: In our study the incidence of GH was 35%. PE characterizes 13% of pregnancies. In 33.3% of CH, 41.4% of GH and 27.3% of PE, diagnosis of chronic hypertension occurred during pregnancy. A significant difference was detected between IC and PE in delivery week (CH 38.5 ± 1.8 vs PE 36.4 ± 1.8, p = 0.008) whereas there were no differences on the type of delivery among the three groups. Proceeding through the pregnancy both OBP and 24h-ABPM showed a gradual increase in BP values. A significant difference was recorded in the first trimester between IC and PE in 24h-SBP (p = 0.036), 24h-DBP (p = 0.04), daily 24h-SBP (p = 0.036) and nocturnal 24hSBP (p = 0.019) contrary to what happened to OBP. The average number of drugs at start of pregnancy resulted comparable among the three groups (CH and GH = 1.4, PE = 1.5), while in the course of pregnancy, the drug load was significantly higher in PE compared to CH and GH (p = 0.015). Conclusions: Our data confirm the need to give birth before term in women with PE. We also showed how an early use of 24h-ABPM could help to identify among patients suffering for CH those at hih risk to develop GH or PE.